The development of word recognition and its significance for comprehension and fluency - Nunes, T; Bryant, P; Barros, R (2012)
When children start to learn to read English, they benefit from learning grapheme-phoneme correspondences. As they become more skilled, they use larger graphophonic units and morphemes in word recognition and spelling. We hypothesized that these 2 types of units in decoding make independent contributions to children's reading comprehension and fluency and that the use of morphological units is the stronger predictor of both measures. In a longitudinal study with a large sample in the United Kingdom, we tested through multiple regressions the contributions that these different units make to the prediction of reading competence (reading comprehension and fluency). The predictors were measured when the children were aged 8-9 years. Reading comprehension and rate were measured concurrently, and reading list fluency was measured at 12 and 13 years. After controlling for age and verbal IQ, the children's use of larger graphophonic units and their use of morphemes in reading and spelling made independent contributions to predicting their reading comprehension and reading fluency. The use of morphemes was the stronger predictor in all analyses. Thus, teaching that promotes the development of these different ways of reading and spelling words should be included in policy and practice. © 2012 American Psychological Association.